Mesenchymal stromal cells from Shwachman‐Diamond syndrome patients fail to recreate a bone marrow niche in vivo and exhibit impaired angiogenesis. (16th May 2018) - Bardelli, Donatella; Dander, Erica; Bugarin, Cristina; Cappuzzello, Claudia; Pievani, Alice; Fazio, Grazia; Pierani, Paolo; Corti, Paola; Farruggia, Piero; Dufour, Carlo; Cesaro, Simone; Cipolli, Marco; et al.
Summary: Shwachman‐Diamond syndrome (SDS) is a rare multi‐organ recessive disease mainly characterised by pancreatic insufficiency, skeletal defects, short stature and bone marrow failure (BMF). As in many other BMF syndromes, SDS patients are predisposed to develop a number of haematopoietic malignancies, particularly myelodysplastic syndrome and acute myeloid leukaemia. However, the mechanism of cancer predisposition in SDS patients is only partially understood. In light of the emerging role of mesenchymal stromal cells (MSCs) in the regulation of bone marrow homeostasis, we assessed the ability of MSCs derived from SDS patients (SDS‐MSCs) to recreate a functional bone marrow niche, taking advantage of a murine heterotopic MSC transplant model. We show that the ability of semi‐cartilaginous pellets (SCPs) derived from SDS‐MSCs to generate complete heterotopic ossicles in vivo is severely impaired in comparison with HD‐MSC‐derived SCPs. Specifically, after in vitro angiogenic stimuli, SDS‐MSCs showed a defective ability to form correct networks, capillary tubes and vessels and displayed a marked decrease in VEGFA expression. Altogether, these findings unveil a novel mechanism of SDS‐mediated haematopoietic dysfunction based on hampered ability of SDS‐MSCs to support angiogenesis. Overall, MSCs could represent a new appealing therapeutic target to treat dysfunctional haematopoiesis in paediatric SDS patients.